Fifteen-minute consultation: an approach to a child presenting to the emergency department with acute psychotic symptoms. Issue 4 (8th December 2017) - Israni, Anil Vasudev; Kumar, Sumant; Hussain, Nahin
Abstract : Presentation of a child in the A&E with altered behaviour including psychotic features is not unusual. New-onset psychotic symptoms in children pose a significant diagnostic challenge due to several reasons. First, primary psychotic conditions are uncommon in pre-pubertal children. Second, differentiating between delirium and psychosis can be difficult in children, more so in infants, toddlers and young children. Third, intervening and managing a secondary cause of psychosis can significantly optimise outcome. Prompt recognition of a possible underlying cause for a child's psychotic behaviour is essential, and at the same time challenging, in the emergency department. This article attempts to present a systematic approach to a child with acute onset of psychotic symptoms in an emergency setting.